Activity typologies as a design model for the ubiquitous detection of daily routines - Jaana Leikas; Helena Launiainen; Minna Kulju; Pertti Saariluoma; Kari Bäckman (Finnish Social and Health Informatics Association, 2018)
Emerging technologies open up new visions and business potential for systems design and development in the areas of wellbeing and health. New technologies enable the detection of human performance and early changes in physical and cognitive functioning, making it possible to monitor an older person's wellbeing. This kind of technology or service sets significant requirements for design, as design concepts must be able to capture the complexity of people's daily lives in terms of activities and environments. Technology itself is "blind" unless designers can adapt it to human life. There is thus a distinct need for comprehensive design and development models that generate adequate human requirements for such design. Activity typologies described in this paper are an example of such life-based design relevant knowledge. They allow the detection of signals in daily routines that would predict a decline in the target person's functioning, and feed this data into design processes. They can be used to create a model for human requirements specification for such ubiquitous services that are grounded on the idea of detecting changes in human activity. The model presented in this paper is created in BeWell project and based on the theoretical frameworks of Life-Based Design and International Classification of Functioning, Disability and Health.